Angioedema with haloperidol: a case report - Costa, Ana Lúcia Rodrigues; Jesus, Sabrina; Almeida, Mónica; Alcafache, João (Revista de Medicina, 2022)
Haloperidol is a first-generation antipsychotic and one of the most commonly used drugs within this category. It is a potent centrally acting antagonist of type 2 dopamine receptors, with low anti-alpha-1-adrenergic activity and no antihistaminic or anticholinergic activity, regularly used in cases of agitation. Angioedema is an especially serious side effect, characterized by marked edema of the subcutaneous or submucosal tissue, and can affect various parts of the body, and may even culminate, in the most severe cases, in death. It has already been described with the administration of several antipsychotics, such as clozapine, risperidone, ziprasidone, and chlorpromazine, but it is rare as a result of administration of haloperidol, occurring in <1% of cases. This article aims to describe the development of angioedema in a patient with acute confusional syndrome after the second administration of IM haloperidol for symptomatic control of agitation in an emergency department setting.